Designing Storyboard for Teaching Writing on Recount Text at Grade Tenth - Regiesta Ardila; Dewi Murni; Satria Agust (Juliet, 2023)
This research was conducted with the objective of creating learning media for teaching writing skills to tenth-grade students at SMAN 5 Batam. The main focus was on designing a storyboard learning media that would enhance student’s motivation to learn writing, making the learning process more engaging and encouraging active participation, especially in writing recount texts. The researcher concentrated on the topic of recount texts for tenth-grade students. The research and development (R&D) approach was employed, utilizing the ADD model by Dick & Carry, which consisted of three stages: analyzing, designing, and development. Data were gathered through interviews and validation sheets. The storyboard teaching materials successfully met the validity criteria, with material validation scoring 82,2% and media validation scoring 80%. Consequently, the storyboard-based teaching materials were deemed suitable for implementation in the classroom to enhance students learning.